2021
DOI: 10.3389/fmed.2021.749318
|View full text |Cite
|
Sign up to set email alerts
|

Liver Histopathological Analysis of 24 Postmortem Findings of Patients With COVID-19 in China

Abstract: Although the pathologic investigation of liver injury was observed in a couple of cases in China, the detailed description of liver histopathologic and ultrastructural changes in a relatively larger series of liver tissues from COVID-19 patients is lacking. Samples from the liver were obtained from 24 COVID-19 cases from February 1 to April 1, 2020. Light microscopy showed that all liver sections had different degrees of liver injury manifested as swelling of the hepatocytes, hepatocellular necrosis, steatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Besides macrovesicular and microvesicular steatosis, microthrombotic pathology dominated in the liver accompanied by activation of intrahepatic stem cell compartment and features of aberrant regeneration 24. Not all liver histopathological studies showed detectable virus particles in the liver 25. In this autopsy study, 42% of patients (n=24) exhibited evidence of severe hepatic necrosis, obviously a key histological feature besides macrovesicular/microvesicular steatosis, data which are also supported by a recent systematic review 26.…”
Section: Covid-19: Liver Manifestations and Pathophysiological Aspectssupporting
confidence: 74%
“…Besides macrovesicular and microvesicular steatosis, microthrombotic pathology dominated in the liver accompanied by activation of intrahepatic stem cell compartment and features of aberrant regeneration 24. Not all liver histopathological studies showed detectable virus particles in the liver 25. In this autopsy study, 42% of patients (n=24) exhibited evidence of severe hepatic necrosis, obviously a key histological feature besides macrovesicular/microvesicular steatosis, data which are also supported by a recent systematic review 26.…”
Section: Covid-19: Liver Manifestations and Pathophysiological Aspectssupporting
confidence: 74%
“…Immunohistochemistry for SARS-CoV-2 highlighted portal macrophages in 5 of 17 cases in the study by Zhao and other. [ 69 ] By electron microscopy, viral particles were not identified in one series of 24 cases, [ 70 ] but others reported virion-like particles in their cases. [ 69 ] In rare reports of patients with liver injury presumably due to COVID-19, some biopsies have demonstrated viral antigens by ISH [ 43 , 71 ] as well as electron microscopy, [ 43 ] suggesting the SARS-CoV-2 can directly infect the liver.…”
Section: Mechanisms Of Gastrointestinal and Hepatobiliary Injurymentioning
confidence: 99%
“…Several studies have also reported important vascular changes including vascular thrombosis and periportal herniation of the portal vein (24,25). On cellular level, hepatocyte ballooning, dilatation of the sinusoids and Kupffer cell proliferation/hyperplasia have been commonly observed (24,25).…”
Section: Histologic Findings and Mechanisms Inducing Liver Injury In ...mentioning
confidence: 99%
“…Several studies have reported a wide variety of pathologic findings in liver histology of patients with COVID-19 [24,25]. The most fre- quent is the presence of micro-and macrovesicular steatosis.…”
Section: Histologic Findings and Mechanisms Inducing Liver Injury In ...mentioning
confidence: 99%
See 1 more Smart Citation